Tingkat Produktivitas Dan Kolaborasi Penulis Pada Jurnal Bulletin Of Scientific Contribution Fakultas Geologi UNPAD Tahun 2015-2019: Analisis Bibliometrika - Yunus Winoto; Nabilla Nada Nafissa (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2023)
This study aims to determine the level of productivity and collaboration of the authors. This research was conducted in the journal Bulletin of Scientific Contribution, Faculty of Geology, UNPAD during the 2015-2019 range. The method used in this research is descriptive qualitative method with bibliometric analysis. For data processing by recording and classifying the number of articles and authors, the level of collaboration and the distribution of productive authors. Based on the results of the study, it is known that the level of author collaboration and author productivity in the journal Bulletin of Scientific Contribution, Faculty of Geology, Padjadjaran University during the 2015-2019 range has published as many as 9 journal publications with an average of 10 articles published in each volume with the language used mostly using Indonesian. The number of authors who contributed to the Bulletin of Scientific Contribution journal is 199 authors and some of the authors are collaborative authors consisting of 3 authors. As for the level of collaboration of the authors is equal to 0.95. This illustrates that the writing of scientific articles in this journal is done more collaboratively than individually.